2019
DOI: 10.25186/cs.v14i2.1582
|View full text |Cite
|
Sign up to set email alerts
|

50 Management of Coffee Leaf Miner: Spray Volume, Efficacy of Cartap Hydrochloride and Impact on Parasitism

Abstract: The leaf miner is a key pest of coffee and the use of insecticides for its control results in high water consumption. The objective in this study was to evaluate the quali-quantitative aspects of reduced spray volumes with and without the addition of adjuvant, the efficacy of the insecticide cartap hydrochloride in the control of the pest and its effects on the parasitism. Two experiments were carried out in coffee plantations in São Desiderio, BA. Initially, solution of Brilliant Blue tracer (0.15% p v-1) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For spray deposition levels, the model was positive line ar, which best explained the variations, with deposit in crements due to increased application rates (Figure 3). The se results were expected, since the spraying of larger sp ray volumes frequently results in larger deposits, as alre ady verified in coffee leaves (Rodrigues et al, 2012;Melo et al, 2019) and fruits (Miranda et al, 2012).…”
Section: Quantitative Assessment Of Spray Applicationsmentioning
confidence: 58%
See 3 more Smart Citations
“…For spray deposition levels, the model was positive line ar, which best explained the variations, with deposit in crements due to increased application rates (Figure 3). The se results were expected, since the spraying of larger sp ray volumes frequently results in larger deposits, as alre ady verified in coffee leaves (Rodrigues et al, 2012;Melo et al, 2019) and fruits (Miranda et al, 2012).…”
Section: Quantitative Assessment Of Spray Applicationsmentioning
confidence: 58%
“…Beta-cypermethrin was classified as harmless at 15 DAA in all volumes, toxic at 30 DAA only at volume of 80.2 L ha -1 and moderately toxic at 28.1, 80.2 and 180.0 L ha -1 (Table 8). With regard to cartape hydrochloride, often used as a standard insecticide for the control of leaf miner, Melo et al (2019) observed reduction in parasitism using higher insecticide application rates (146 and 309 L ha -1 ) with the addition of adjuvant until 15 DAA in coffee cultivation in the western region of Bahia, which is considered toxic to pest parasites. However, these results are in disagreement with those observed in the study, as cartape hydrochloride is toxic at 15 DAA at lower application rates (28.1 and 80.2 L ha -1 ).…”
Section: Impact On Natural Parasitismmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays the chemical control of CLM is mandatory for the maintenance of coffee crops. There are some active ingredients available and the most efficient are thiamethoxan [2], chlorantraniliprole [40], cartap hydrochloride [41]. Studies on the stability of those products detected their presence in plants up to eight and six months after application, respectively.…”
Section: Control and Management Of The Clmmentioning
confidence: 99%